Engaging humor - Oring, Elliott, 1945- (Book collections on Project MUSE., 2003)
In Engaging Humor, Elliott Oring asks essential questions concerning humorous expression in contemporary society, examining how humor works, why it is employed, and what its messages might be. This provocative book is filled with examples of jokes and riddles that reveal humor to be a meaningful--even significant--form of expression._x000B_ _x000B_Oring scrutinizes classic Jewish jokes, frontier humor, racist cartoons, blonde jokes, and Internet humor. He provides alternate ways of thinking about humorous expressions by examining their contexts--not just their contents. He also shows how the incongruity and absurdity essential to the production of laughter can serve serious communicative ends._x000B_ _x000B_Engaging Humor examines the thoughts that underlie jokes, the question of racist motivation in ethnic humor, and the use of humor as a commentary on social interaction. The book also explores the relationship between humor and sentimentality and the role of humor in forging national identity. Engaging Humor demonstrates that when analyzed contextually and comparatively, humorous expressions emerge as communications that are startling, intriguing, and profound.